Research on Performance Analysis of Art Ceramics Based on Different Composition Contents. Issue 2 (December 2018) - Wu, Xiumei
Abstract: Objective: To analyze the mechanical properties of ceramics and the effect of wear resistance after adding different amounts of ZrO2 in Al2 O3 ceramic materials, so as to obtain the optimum amount of ZrO2 in Al2 O3 ceramics. METHODS: Al2 O3 ceramics were prepared by hot pressing bantering. The first group used 99.6 vol% Al2 O3, the second group used 15 vol% ZrO2 in Al2 O3, and the third group used 25 vol% ZrO2 in Al2 O3 . In order to meet the memo-mechanical theory of materials and fully consider the phase transition characteristics of ZrO2, a mechanical structure model between the two is established. RESULTS: After the addition of refined zircon crystals to the alumina material, the compactness of the ceramic material was significantly improved. The mechanical properties of the ceramic materials produced in the three experiments showed a linear relationship of stress-strain curves. The fracture toughness of the first group of ceramics is 5.38 MPa⋅m 0.5, and the fracture toughness of the second group of ceramics is 8.37 MPa⋅m 0.5, which is about 50% higher than the fracture toughness of the previous set of experiments; the third group of experimental sites the fracture toughness of the obtained ceramic material was 10.53 MPa⋅m 0.5 . Conclusion: Further explanation, accompanied by an increase in the increase in ZrO2 . The elastic modulus of ceramics decreases and the fracture toughness increases. This trend is in good agreement with the experimental results. The wear form without increasing the ZrO2 material layer is mainly abrasive wear, and the wear of the ZrO2 material layer is mainly adhesive wear.